Co-occurrence of cytogenetic abnormalities and high-risk disease in newly diagnosed and relapsed/refractory multiple myeloma - Kaiser, Martin Florian; Sonneveld, Pieter; Cairns, David A.; Raab, Marc-Steffen; Izquierdo, Jesús San-Miguel; Zhang, Rick; Acosta, Jorge; Larocca, Alessandra; Popat, Rakesh; Li, Cong; Bärtsch, Marc-Andrea; Brown, Sarah R.; et al. (Journal of clinical oncology, 2025)
PURPOSE: Survival for patients with multiple myeloma (MM) has improved but outcomes remain heterogeneous. Consistent diagnostic identification of high-risk disease is desirable to address unmet patient need. The aim was to investigate the consistency of association of co-occurrence of high-risk cytogenetic abnormalities (HRCAs) with prognosis in patients with newly diagnosedMM(NDMM) and relapsed/refractory MM (RRMM), and across a range of treatment modalities. METHODS: A systematic review of randomized controlled trials ofMMthat reported testing for HRCA between January 1, 2000, and December 9, 2021, was performed. Groups were contacted and asked to locally perform a novel, federated analysis of their data for single hit (one HRCA) and double hit (≥two HRCAs), using a centrally provided algorithm. Analysis results were centrally collated and metaanalyzed to assess the hazard ratio (HR) for progression-free survival (PFS) and overall survival (OS) for one/≥two HRCAs across patient subgroups using random-effects models.RESULTS: Twenty-four trials including 13,926 patients were included. The median age of participants was 66.5 years (IQR, 59-72) and 56.5% were male (IQR, 52-60). The HR for PFS was 2.28 (95% CI, 2.05 to 2.54) for patients with ≥two HRCAs and 1.51 (95% CI, 1.38 to 1.65) for patients with one HRCA. The HR for OS was 2.94 (95% CI, 2.49 to 3.47) and 1.69 (95% CI, 1.52 to 1.88) for the two subgroups, respectively. In studies initiated since 2015, the effect abides (≥two HRCA PFS, HR, 2.39 [95% CI, 1.96 to 2.91]; OS, 3.10 [95% CI, 2.10 to 4.60]) both for NDMM and RRMM. Heterogeneity related to transplant eligibility and relapsed/refractory status was as expected. CONCLUSION: The association of ≥two HRCAs with the poorest outcome inNDMMand RRMM, and across treatment modalities, as demonstrated here for the first time to our knowledge, allows for more focused development of novel approaches to these patients with high unmet need.
Online veröffentlicht: 18. Februar 2025
Gesehen am 21.01.2026